Hot off the press. Issue 10 (20th September 2019) - Hill, Robert A.; Sutherland, Andrew
Abstract : A personal selection of 32 recent papers is presented covering various aspects of current developments in bioorganic chemistry and novel natural products such as phlegmadine A from Phlegmariurus phlegmaria . Abstract : A personal selection of 32 recent papers is presented covering various aspects of current developments in bioorganic chemistry and novel natural products such as phlegmadine A from Phlegmariurus phlegmaria .